Wahdat al-Wujud’s Doctrine of Hamzah al-Fansuri in Javanese Literature: The Identity of Unity of Being in a Manuscript Entitled Miftah al-Mannan - Zuhri; Ghozali, Mahbub; Nafisah, Lailiyatun; Usman, Ali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The syncretic doctrine of the unity of being of kejawen (Javanese mysticism) influence is predominant in the teachings of mysticism in Java. The unity of being, which is closely related to the doctrine of Sufism, is apparent in Miftah al-Mannan, which teaches the unity of being through tariqah (path of purity) mechanism. The totality of being by denying all forms of being other than God illustrates the doctrine leading to the controversial pantheism of al-Fansuri. Analysis of the content of Miftah al-Mannan can prove that al-Fansuri’s influence extends to various regions in Indonesia. This study aims to identify such extensive influence through a qualitative method using content analysis. The research revealed that the doctrine of the unity of being in Miftah al-Mannan is identical to the concept brought about by al-Fansuri, which denies being in the process of unity of being. Both concepts principally share similarities that underpin the unity of being due to a single source of events. God manifests Himself to all of His creation. To achieve the unity of being, the salik (traveler) is required to take shari‘ah to achieve haqiqah (truth) by means of tariqah (path of purity). The pantheistic unity of being indicates the expansion of al-Fansuri’s influence on the Java region. The existence of al-Fansuri’s doctrine also demonstrates that the doctrine of wujudiyah in Java is not only dominated by the syncretic and kejawen concept of manunggaling kawulo gusti (the unity between human soul and God).